Structural equation model of the adoption of ozone generator technology by thai industries - Potivejkul, Siriwat; Phimolsathien, Thepparat; Pimdee, Paitoon (My University, 2015)
Ozone is second only to fluorine as the most powerful oxidant in the world. It's the most powerful, natural air and water sanitizer readily available and can break down chemicals into their basic naturally-occurring component parts. The objectives of this study were therefore, to test a model of technology adoption used in the ozone generator industry in Thailand. Self-reporting questionnaires were retrieved from 500 production and engineering managers in both central and eastern Thailand enterprises from a total of 3,000 distributed. The research framework integrates Corporate Vision, Awareness, Interest, Evaluation and Trial to hypothesize a theoretical model to explain and predict adoption of ozone generator technology. All latent variables in the model have a positive influence on the adoption of Thai ozone generator technology. The model furthermore consisted of 18 observed variables with a variable latency of 6 variables which had a positive influence on the adoption of ozone generator technology. The final structural model was verified to achieve a good fit with the empirical data at 65% because of the decision to use new products in ozone generator technology. Using LISREL 8.72 Structural Equation Modeling (SEM), the results showed that that the variables that influence technology use the most are Adoption, followed by Interest and Evaluation, followed by Trial, Awareness and Corporate Vision having the effects of 0.73, 0.53, 0.42, 0.31 and 0.23, respectively.
Keywords: Industrial sector; Ozone generators; Structural equation model; Technology adoption; Thailand